Non-Conviction Based Asset Forfeiture (NCBAF) as an Asset Recovery Instrument in Indonesia: Juridical Analysis and Justice Perspective - Wahyudi Wahyudi; Muhammad Islahuddin (Rechtsvinding, 2026)
The confiscation of assets resulting from criminal acts is an important instrument in supporting the eradication of crime oriented to economic profit. This research focuses on a juridical analysis of the Non-Conviction Based Asset Forfeiture (NCBAF) mechanism as an instrument of asset forfeiture without a criminal verdict and its relevance in realizing justice in the Indonesian legal system. The purpose of the study is to analyze the legal basis, implementation mechanism, and potential of NCBAF in supporting the effectiveness of asset recovery. This research uses normative legal methods with laws and regulations, conceptual, and case approaches. Data were obtained through literature studies on primary, secondary, and tertiary legal materials, then analyzed qualitatively by descriptive-analytical methods. The results show that NCBAF has a normative foundation in UNCAC, UNTOC, and FATF recommendations, but has not been comprehensively regulated in the Indonesian legal system. The implications of the study confirm the need for special regulations regarding NCBAF to strengthen the effectiveness of asset recovery while ensuring legal certainty, protection of property rights, and the principle of due process of law.